EMPLOYEE PERFORMANCE MODEL: WORK ENGAGEMENT THROUGH JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT (A STUDY OF HUMAN RESOURCE MANAGEMENT LITERATURE STUDY) - Yandi, Andri; Bimaruci Hazrati Havidz, Hazimi (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence employee performance, namely: job involvement through job satisfaction and organizational commitment, a study of Human Resource Management literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) job involvement (X) has an effect on employee job satisfaction (M1); 2) work involvement (X) has an effect on organizational commitment (M2); 3) work involvement (X) affects employee performance (Y); 4) job satisfaction (M1) has an effect on employee performance (Y); 5) organizational commitment (M2) has an effect on employee performance (Y); 6) work involvement (X) through job satisfaction (M1) has an effect on employee performance (Y); and 7) work involvement (X) through organizational commitment (M2) has an effect on employee performance (Y).